(untitled) (Research, Society and Development, 2024)
The present study aimed to evaluate the clinical and epidemiological profile of patients with migraine treated at the neurology outpatient clinic of a University Hospital. It was a quantitative, descriptive, observational, and retrospective study involving adult patients diagnosed with migraine, treated from 1st January to 31st December 2021. Sociodemographic and clinical information was collected from medical records. A total of 247 patients were included, predominantly women (93.5%), with an average age of 43.7 years, married (48.6%), with no family history (56.0%) or previous treatment (57.7%). About 74.9% reported comorbidities, with hypertension (26.2%) and psychiatric disorders (12.6%) being the most prevalent. There was a significant association between the number of migraine days per month and the presence of comorbidities (p< 0.05) and between chronic migraine and comorbidities (OR 2.65). This research characterised the clinical and epidemiological profile of the patients, confirming that comorbidities are associated with the chronification of migraine and interfere with daily activities.